Advances in biological markers of ferroptosis in myocardial infarction - CHANG Yuchen, LI Jingbo (Zhenduanxue lilun yu shijian, 2023)
The development in diagnosis and treatment of myocardial infarction has significantly improved the prognosis of some patients, while the overall survival rate of patients remains much room for improvement. Further research of the mechanism of injury after myocardial ischemia and reperfusion may explore new directions of research. As a newly discovered form of regulated cell death, ferroptosis, an iron-dependent cell death caused by lipid peroxidation, which has been characterized by cell death involving the accumulation of lipid peroxides and reactive oxygen species. Ferroptosis, which has been acknowledged to play an important role in ischemia-reperfusion injury. Studies suggest that iron death-related marker changes after myocardial infarction (MI), including hiatus of mitochondrial ferritin (FtMt) in intracellular iron metabolism, decreased levels of glutathione peroxidase 4 (Gpx4), a terminal molecule of glutathione metabolism pathway, insufficient use of antiporter cystine/glutathione synthesis (SXc-) in glutathione synthesis, and overexpression of Acyl-CoA synthetase long-chain family member 4 (ACSL4) can lead to oxidative stress, inflammatory response, cardiomyocyte injury after myocardial infarction, and can aggravate the myocardial ischemia-reperfusion injury. The four biological markers mentioned above, FtMt, Gpx4, SXc- and ACSL4, are important research targets for the diagnosis and treatment of iron death after MI, which may deserve further study.